The Mosaic Architecture of NRPS-PKS in the Arbuscular Mycorrhizal Fungus Gigaspora margarita Shows a Domain With Bacterial Signature - Venice, Francesco; Desirò, Alessandro; Silva, Gladstone; Salvioli, Alessandra; Bonfante, Paola (Frontiers in Microbiology, 2020)
As obligate biotrophic symbionts, arbuscular mycorrhizal fungi (AMF) live in association with most land plants. Among them, Gigaspora margarita has been deeply investigated because of its peculiar features, i.e. the presence of an intracellular microbiota with endobacteria and viruses. The genome sequencing of this fungus revealed the presence of some hybrid Non-Ribosomal Peptide Synthases-Polyketide synthases (NRPS-PKS) that have been rarely identified in AMF. The aim of this study is to describe the architecture of these NRPS-PKS sequences and to understand whether they are present in other fungal taxa related to G. margarita. A phylogenetic analysis shows that the Ketoacyl Synthase (KS) domain of one G. margarita NRPS-PKS clusters with prokaryotic sequences. Since horizontal gene transfer (HGT) has often been advocated as a relevant evolutionary mechanism for the spread of secondary metabolite genes, we hypothesized that a similar event could have interested the KS domain of the PKS module. The bacterial endosymbiont of G. margarita, Candidatus Glomeribacter gigasporarum (CaGg), was the first candidate as a donor, since it possesses a large biosynthetic cluster involving an NRPS-PKS. However, bioinformatics analyses do not confirm the hypothesis of a direct HGT from the endobacterium to the fungal host: indeed, endobacterial and fungal sequences show a different evolution and potentially different donors. Lastly, by amplifying a NRPS-PKS conserved fragment and mining the sequenced AMF genomes, we demonstrate that, irrespective of the presence of CaGg, G. margarita and some other related Gigasporales possess such a sequence.